Mechanism of 6H-3C transformation in SiC - Vlaskina, S.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Heavily doped by nitrogen single crystals of 6H-SiC were completely transformed into 3C-SiC ones by annealing in vacuum at presence of Si vapor for 1 hour at 2180 K or 4 hours at 2080 K. Mechanism of solid-to-solid transformation have been studied. Calculated nitrogen concentration from the Hall effect and EPR spectra for transformed crystals show its decreasing value in 3C-SiC. Data show appearance of new defects - donors and acceptors - that make nitrogen optically and electrically non-active. These defects accompany the process of transformation.